2011
DOI: 10.1371/journal.pone.0017387
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Channel Polymorphisms Are Associated with the Somatosensory Function in Neuropathic Pain Patients

Abstract: Transient receptor potential channels are important mediators of thermal and mechanical stimuli and play an important role in neuropathic pain. The contribution of hereditary variants in the genes of transient receptor potential channels to neuropathic pain is unknown. We investigated the frequency of transient receptor potential ankyrin 1, transient receptor potential melastin 8 and transient receptor potential vanilloid 1 single nucleotide polymorphisms and their impact on somatosensory abnormalities in neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 38 publications
(54 reference statements)
3
99
0
3
Order By: Relevance
“…I315M was associated with cold hypoesthesia (Binder et al, 2011). Although they found no evidence that TRP genetic variants are associated specifically with the prevalence of neuropathic pain, the polymorphisms contributed significantly to the somatosensory abnormalities that are experienced by patients with neuropathic pain (Binder et al, 2011).…”
Section: Transient Receptor Potential Vanilloid 1 Polymorphismsmentioning
confidence: 96%
See 1 more Smart Citation
“…I315M was associated with cold hypoesthesia (Binder et al, 2011). Although they found no evidence that TRP genetic variants are associated specifically with the prevalence of neuropathic pain, the polymorphisms contributed significantly to the somatosensory abnormalities that are experienced by patients with neuropathic pain (Binder et al, 2011).…”
Section: Transient Receptor Potential Vanilloid 1 Polymorphismsmentioning
confidence: 96%
“…Although they found no evidence that TRP genetic variants are associated specifically with the prevalence of neuropathic pain, the polymorphisms contributed significantly to the somatosensory abnormalities that are experienced by patients with neuropathic pain (Binder et al, 2011). Further investigation into TRPV1 SNPs and neuropathic pain conditions may be useful, but these very recent studies show that variations in TRPV1 can explain some of the CAPSAICIN: TO UNDERSTAND AND TREAT PAIN variability in pain seen in patients with pathophysiological conditions.…”
Section: Transient Receptor Potential Vanilloid 1 Polymorphismsmentioning
confidence: 99%
“…Data for estimates of IC 50 from treatments performed in triplicate on three separate occasions and include + − S.D. The AMTB IC 50 value for non-mutated information regarding gene sequence variation, suggest that further screening of the properties of variants may aid implementation of targeted clinical studies [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Our work highlights some functional consequences of naturally occurring genetic TRPA1 variants. Some evidence for modulation of human pain behavior by genetic variants in the TRPA1 gene has been published previously (5,11,12,22). Recently, we observed that the change of a glutamate residue to lysine at TRP peptide position 179 (E179K) diminished occurrence of PHS in patients suffering from neuropathic pain (12).…”
Section: Discussionmentioning
confidence: 67%
“…They described a N855S gain-of-function mutation in the S4 transmembrane segment of TRPA1, which resulted in increased activation of the ion channel by noxious cold temperature underlining the contribution of genetics in pain plasticity (11). Recently, we identified the nonsynonymous genetic variant E179K (rs920829) of the human TRPA1 gene to be associated with the occurrence of paradoxical heat sensation (PHS) 2 in neuropathic pain patients (12). PHS is defined as a burning heat sensation when a noxious cold stimulus is applied.…”
mentioning
confidence: 99%